Borderline personality disorder under a functional analytic perspective (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
In this paper, it will be demonstratedhowa radical behaviorally based approach to psychotherapy, Functional Analytic Psychotherapy, treats a specific personality disorder which is known as Borderline Personality Disorder. The present work points out the relevance of a functional analysis of the individual history, the present moment and therapeutic relationship, to understand and treat the client's problems. The therapeutic relationship is described as a powerful tool to change the client's behaviors. This procedure argues that when somebody behaves, in the session, the same way as in his daily life with other people those settings are functionally similar. This way if there is a change in one of those settings, this modification will generalize to the others. This paper illustrates the case of a clientwhois 34 years old with Borderline Personality Disorder. The sessions were held once a week, and each session lasted two hours. There was transference and the therapeutic relationship could change client's behaviors in the session and on her daily life.